Aromatic molecular junctions between graphene sheets: a molecular dynamics screening for enhanced thermal conductance. Issue 27 (17th May 2019) - Di Pierro, Alessandro; Bernal, Maria Mar; Martinez, Diego; Mortazavi, Bohayra; Saracco, Guido; Fina, Alberto
Abstract : The tuning of covalently bound molecular junctions could increase heat transfer between graphene platelets inside nanocomposites materials. Abstract : The proper design and synthesis of molecular junctions for the purpose of establishing percolative networks of conductive nanoparticles represent an opportunity to develop more efficient thermally-conductive nanocomposites, with several potential applications in heat management. In this work, theoretical classical molecular dynamics simulations were conducted to design and evaluate thermal conductance of various molecules serving as thermal bridges between graphene nanosheets. A wide range of molecular junctions was studied, with a focus on the chemical structures that are viable to synthesize at laboratory scale. Thermal conductances were correlated with the length and mechanical stiffness of the chemical junctions. The simulated tensile deformation of the molecular junction revealed that the mechanical response is very sensitive to small differences in the chemical structure. The analysis of the vibrational density of states provided insights into the interfacial vibrational properties. A knowledge-driven design of the molecular junction structures is proposed, aiming at controlling interfacial thermal transport in nanomaterials. This approach may allow for the design of more efficient heat management in nanodevices, including flexible heat spreaders, bulk heat exchangers and heat storage devices.